Recovery of lead from by-products of the bismuth refining by metallothermic reduction treatments - Vladislav Matković; Branislav Marković; Miroslav Sokić; Vaso Manojlović (Zaštita Materijala)
In the refinement process of bismuth by chlorinating of Bi-Pb alloy (Kroll-Betterton process) as a by-product lead chloride is formed. This study was focused on the lead valorization from PbCl 2 by aluminothermic and zincothermic reduction. Besides lead, as a main product, during aforementioned process technical grade alumina (aluminothermic reduction) and ZnCl2 (zincothermic reduction) were also obtained. The secondary aluminium and zinc of different granulometry were used as a reducent. The effect of temperature, time, granulometry of reducents and stirring speed (zincothermic reduction) on the lead recovery was investigated. Based on the experimental results, the optimal process parameters were defined. Recovery of crude lead (containing 98%Pb) was in the range 95-98% for aluminothermic reduction and 85-90% for zincothermic reduction. The crude lead can be further processed in lead smelters. Technical grade alumina was used in ceramic industry, wile zinc-chloride is suitable for hydrometallurgical treatment giving 50 % solution of zinc-chloride as the final product.